2010
DOI: 10.3390/polym2030188
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Induced Solubility Transitions of Various Poly(2-oxazoline)s in Ethanol-Water Solvent Mixtures

Abstract: Abstract:The solution behavior of a series of poly(2-oxazoline)s with different side chains, namely methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, pentyl, hexyl, heptyl, octyl, nonyl, phenyl and benzyl, are reported in ethanol-water solvent mixtures based on turbidimetry investigations. The LCST transitions of poly(2-oxazoline)s with propyl side chains and the UCST transitions of the poly(2-oxazoline)s with more hydrophobic side chains are discussed in relation to the ethanol-water solvent compositio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 68 publications
(65 citation statements)
references
References 57 publications
2
62
1
Order By: Relevance
“…While the E moduli decreased linearly with an increasing number of carbon-atoms in the side-chain of amorphous polymers, semicrystalline polymers by contrast do not display any correlation between the E modulus and the length of the side-chain. Schubert, Hoogenboom and co-workers also reported on the solubility transitions in ethanol-water binary mixtures for a series of homopoly(2-oxazoline)s, comprising the eight congeners of the just-above mentioned study as well as p i PrOx, p i BuOx, p n OctOx, pPhOx, and pBzOx [135]. As expected, the solubility of the polymers correlated with the length of the side-chain.…”
Section: Synthesis Of Monomers and The Corresponding Poly(2-oxazoline)smentioning
confidence: 62%
“…While the E moduli decreased linearly with an increasing number of carbon-atoms in the side-chain of amorphous polymers, semicrystalline polymers by contrast do not display any correlation between the E modulus and the length of the side-chain. Schubert, Hoogenboom and co-workers also reported on the solubility transitions in ethanol-water binary mixtures for a series of homopoly(2-oxazoline)s, comprising the eight congeners of the just-above mentioned study as well as p i PrOx, p i BuOx, p n OctOx, pPhOx, and pBzOx [135]. As expected, the solubility of the polymers correlated with the length of the side-chain.…”
Section: Synthesis Of Monomers and The Corresponding Poly(2-oxazoline)smentioning
confidence: 62%
“…Finally, a study was recently reported by Hoogenboom and Schubert on the solubility behavior of poly(2-(n-alkyl)-2-oxazoline) in ethanol-water solvent mixtures clearly demonstrating the effect of side-chain length on the solubility [33]. Poly(2-oxazoline)s with methyl, ethyl, and propyl side chains were found to be soluble in all possible combinations of water and ethanol, whereby poly(2-(n-propyl)-2-oxazoline) revealed LCST behavior in water rich solvent mixtures.…”
Section: Systematical Variations In Side-chain Lengthmentioning
confidence: 66%
“…[103] The ethanol content required to induce UCST transitions increases with increasing hydrophobicity of the polymer side chains. The evolution of the UCST cloud points was ascribed to the hydrophilic-hydrophobic balance of the side groups of the polymers on the one hand and the ethanol-water solvent structure on the other hand (see section 2).…”
Section: 2mentioning
confidence: 99%